The Effect Of Regional Financial Accounting Systems And Utilization Of Information Technology On SKPD Performance With Attitude Of Government Apparatuses As A Moderating Variable - Rio Johan; Afifah Rahmawati (Publikasi Indonesia, 2023)
This study aims to test whether the moderation of the attitude of government officials can influence the regional financial accounting system and the use of information technology on SKPD performance. The population and samples selected in this study were Regional Work Units (SKPD) in the DKI Jakarta area, questionnaires which would be distributed to Regional Work Units (SKPD) in the DKI Jakarta area with a total of 236 samples. The software used is SmartPLS (Partial Least Square). The results of hypothesis testing in this study found that the regional financial accounting system has a positive and significant effect on SKPD performance, the use of information technology has a positive effect on SKPD performance, the attitude of government officials on SKPD performance has a positive and significant effect, the attitude of government officials can strengthen the influence of the regional financial accounting system on SKPD performance and moderating the attitude of government officials are not able to strengthen the influence of the use of information technology on SKPD performance.